Discretionary-accruals models and audit qualifications - Bartov, Eli; Gul, Ferdinand A.; Tsui, Judy S.L. (Journal of Accounting and Economics, 2000)
The primary goal of this study is to evaluate the ability of the Cross-sectional Jones Model and the Cross-sectional Modified Jones Model to detect earnings management vis-à-vis their time-series counterparts by examining the association between discretionary accruals and audit qualifications. These two cross-sectional models have not been formally evaluated by prior research, and their use may offer certain advantages to investors and researchers over their time-series counterparts. A sample of 173 distinct firms with qualified audit reports and a matched-pair control sample with clean audit reports are used. Only the two cross-sectional models are consistently able to detect earnings management. One limitation of this study is that its findings merely indicate the superiority of the cross-sectional models vis-à-vis their time-series counterparts in an audit qualification setting, not validate either the former or the latter.